Trans ε-Viniferin Decreases Amyloid Deposits With Greater Efficiency Than Resveratrol in an Alzheimer’s Mouse Model - Freyssin, Aline; Rioux Bilan, Agnès; Fauconneau, Bernard; Galineau, Laurent; Serrière, Sophie; Tauber, Clovis; Perrin, Flavie; Guillard, Jérôme; Chalon, Sylvie; Page, Guylène (Frontiers in Neuroscience, 2022)
In a previous study, we showed that viniferin decreased amyloid deposits and reduced neuroinflammation in APPswePS1dE9 transgenic mice between 3 and 6 months of age. In the present study, wild type and APPswePS1dE9 transgenic mice were treated from 7 to 11 or from 3 to 12 months by a weekly intraperitoneal injection of either 20 mg/kg viniferin or resveratrol or their vehicle, the polyethylene glycol 200 (PEG 200). The cognitive status of the mice was evaluated by the Morris water maze test. Then, amyloid burden and neuroinflammation were quantified by western-blot, Enzyme-Linked ImmunoSorbent Assay (ELISA), immunofluorescence, and in vivo micro-Positon Emission Tomography (PET) imaging. Viniferin decreased hippocampal amyloid load and deposits with greater efficiency than resveratrol, and both treatments partially prevented the cognitive decline. Furthermore, a significant decrease in brain uptake of the TSPO PET tracer [18F]DPA-714 was observed with viniferin compared to resveratrol. Expression of GFAP, IBA1, and IL-1β were decreased by viniferin but PEG 200, which was very recently shown to be a neuroinflammatory inducer, masked the neuroprotective power of viniferin.